Cognitive Barriers to Financial Inclusion: The Differential Impact of Literacy on Savings, Debt, and Investment in Chile - Lozano, Francisco-Javier (Journal of Behavioral Economics and Policy, 2025)
This study investigates the role of financial literacy as a driver of household financial inclusion in Chile, using novel data from the 2024 Household Financial Survey (EFH). Using a probit model with multiple imputations to correct for non-random income non-response, we find that financial literacy is a strong predictor of financial behavior, exhibiting a financial sophistication gradient. Our estimates indicate that a one-point increase in the financial literacy index is associated with a 3.2 percentage point rise in access to consumer credit and a 4.5 percentage point increase in savings. This effect surges to 7.4 percentage points for investment holdings; this identifies cognitive skills as the primary filter for accessing wealth-generating assets. To address endogeneity and omitted variable bias concerns in a formal way, we implement Oster's bounds analysis and several sensitivity tests. The results yield high proportional selection coefficients, confirming that selection on unobservables would need to be significantly higher than selection on observables to invalidate our baseline estimates. Furthermore, rather than implying identical intrinsic risk preferences, our results indicate that controlling for financial human capital attenuates the gender penalty in investment and credit participation, although a gap of 5.7 percentage points persists in savings behavior. These findings support a dual policy approach: utilizing choice architecture for basic inclusion and targeted financial education policies that democratize access to complex financial markets.